Angle-Based Photovoltaic Curve Tracing using Boost Converter - Ayop, R; Tan, C W; Syed Nasir, S N; Nordin, N M; Mahmud, M S A (Journal of physics. Conference series, 2021)
A photovoltaic (PV) curve tracer is equipment that obtains the characteristic curve of the PV that can be used for PV modelling or performance analysis. Currently, the used of the switched-mode power supply in the PV curve tracer application is limited due to the voltage ripple problem. This paper provides the potential and limitation of designing the PV curve tracer using the boost converter. A new angle-based curve tracing algorithm is proposed to produce evenly distributed tracepoints on the PV curve. The PI controller is used to control the boost converter based on the input from the angle-based curve tracing algorithm. The PV curve tracer is simulated using MATLAB/Simulink. The results show that the proposed PV curve tracer is accurate and trace a significant portion of the PV curve.